Choosing the Appropriate Modulation Technique in the Multilevel Converters with Flying Capacitors (PDPWM PODPWM APODPWM) - كارلو مقدسي; منهل صالح (Latakia University Journal -Engineering Sciences Series, 2023)
The use of multilevel converters ML is an advanced step in securing high-quality power supply for loads, and these converters are of great importance when the required load power rate is high. The use of multilevel converters with flying capacitors FCMLI to feed high power loads and high voltages is vital and important that cannot be secured by other structures or topologies such as Cascaded or Diode Clamped Converters. Choosing the appropriate modulation technique plays a major role in determining the shape of the output curves for the voltages and currents feeding the loads, which must be free of distortions or higher harmonics (total harmonic distortion THD less than 5%). In this paper, the modulation techniques (PDPWM PODPWM APODPWM) used with multilevel inverter with flying capacitors is investigated, the best choice of the technology based on a comparison of the total harmonic distortion THD values for phase and linear voltages and currents without and with the use of filters are shown also in this paper, therefore the best modulation technology for the inverter according to the proposed number of levels will be suggested. That is, modeling the multilevel converter with five, seven, and nine levels and testing different modulation techniques at different levels (APODPWM, PDPWM, PODPWM).